Analysis of Discourse Text Forming Islamic Image in Post-212 Action News in Waspada Newspaper - Muhammad Thariq; Syukur Kholil; Iskandar Zulkarnain (Budapest International Research and Critics University, 2020)
This study focuses on the meaning of a Post-Action 212 concept that produces specific texts and media work processes. Like the reverse flow of evidence, this study starts at the text level to identify whether or not there are inconsistencies in meaning, followed by analysis at those levels questioning why the visible and invisible text is behind. The Waspada Daily in the discourse of shaping the image of Islam on Post-Action 212 news tends to show good news (good news) or a positive image, even it seems better than the true goodness (the Islamic concept of rahmatan lil'alamin) that exists in the object itself (news). This is marked by the cognition of journalists and media in the text which selects supporting elements of the main theme. Another cognition can be seen in choosing titles with a variety of rhetoric and ornaments and expressions that state the justification that news is important and interesting as well as showing a pro-Islam media ideology. In addition, it shows the tendency of good news news through content analysis of the main issues presented, such as issues concerning Religion and Sharia 4 news or 36 percent and Peace 3 news or 28 percent, using 4 news or 66 percent of mass organizations / non-government sources as well as the placement of all news on page one and headlines.